Elements of Quantum Computing : History, Theories and Engineering Applications - Akama, Seiki (Springer International Publishing : Imprint: Springer, 2015)
A quantum computer is a computer based on a computational model which uses quantum mechanics, which is a subfield of physics to study phenomena at the micro level. There has been a growing interest on quantum computing in the 1990's, and some quantum computers at the experimental level were recently implemented. Quantum computers enable super-speed computation, and can solve some important problems whose solutions were regarded impossible or intractable with traditional computers. This book provides a quick introduction to quantum computing for readers who have no backgrounds of both theory of computation and quantum mechanics. "Elements of Quantum Computing" presents the history, theories, and engineering applications of quantum computing. The book is suitable to computer scientists, physicist, and software engineers.